The immune system response to the SARS-CoV-2 virus: March 2021 update - Klenerman, Paul (Henry Stewart Talks, 2021)
Biology of the SARS-CoV-2 mutations, T cell response to vaccination, The long-term health effects from a SARS-CoV-2 infection, Current and future treatments for COVID-19, Future work in the field